(untitled) (KULT_online, 2017)
With the monograph Indigenous Elites and Creole Identity in Colonial Mexico, 1500–1800 Peter Villella provides an intellectual history of native Mexican historiography over three centuries. He maps the patterns underlying the historical narrative developed by indigenous authors starting shortly after the Spanish expansion, who drew on their ancestors‘ Aztec past in order to uphold traditional rights. Their arguments are grounded in a close analysis of the changing social and judicial status of Mexican native people. The author argues that interactions between colonial native, Spanish, and creole writers shaped this narrative in constant flux, which continues to inform current Mexican politics and imaginations.